A STUDY ON TEACHING SPEAKING SKILL OF DESCRIPTIVE TEXT IN VOCATIONAL HIGH SCHOOL - Putu Ngurah Rusmawan (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2019)
Teaching speaking of descriptive text in vocational high school should be in systematic way. Based on the syllabus of K13, the students had to master the generic structure and organization in descriptive text. The researcher tried to explore the teaching-learning process in the eleventh grade of SMK Kartika. This research used descriptive qualitative research. It focused on understanding the teaching-learning process from the teacherâ€™s viewpoint of this research. This descriptive research required the researcher to explain scientifically the fact, events, and characteristics of the subject. The teacher had prepared the entire requirement of teaching and learning equipment such as attendance list, syllabus, lesson plan, media, and evaluation form. Then the teacher used the picture a media in teaching speaking descriptive text. Most of the students at eleventh graders could overcome that problem during learning speaking descriptive text. 90 % of students could comprehend the material well and 10% of students could not comprehend the material.Â It indicated that some of the students understood the teacherâ€™s explanation about the descriptive text.